MENALAR PARADOKS KONSEP NASIONALISME, GENERASI EMAS, DAN TEKNOKRASI: PERSPEKTIF ILMU SOSIAL KRITIS - Kenoba, Marianus (Sajaratun : Jurnal Sejarah dan Pembelajaran Sejarah, 2024)
AbstractNationalism constitutes a fundamental concept within modern social sciences. However, its interpretation and system of meaning are not always neutral, often leading to paradoxes. This paradox arises from the notion that pragmatic nationalism is influencing the younger generation, which, by 2045, has been conceptualized within the sociopolitical framework as the "golden generation". This generation is inherently perceived as literate and adaptable to the dynamics of contemporary technological "logic." Nonetheless, the latent danger confronting the golden generation is the "ideology" of technocracy embedded in the application of modern technology. This research aims to internalize the concept of objective nationalism as a foundational basis for the golden generation, thereby mitigating the ideological biases present in technocratic systems. The study employs critical hermeneutics as a methodological approach to interpreting the written texts that serve as the primary references for this research. The findings indicate that critical education regarding objective nationalism is vital for strengthening the character of the younger generation, enabling them to confront the rationalizing threats posed by modern knowledge systems. Consequently, the concept of objective nationalism may function as a proactive instrument for the golden generation in addressing the ideological challenges posed by technocracy.